Activated Carbon Electrodes for Supercapacitors from Purple Corncob ( Zea mays L. ) - Huarote Garcia, Emily (2024)
Activated carbon-based supercapacitor electrodes synthesized from biomass or waste-derived biomass have recently attracted considerable attention because of their low cost, natural abundance, and power delivery performance. In this work, purple-corncob-based active carbons are prepared by KOH activation and subsequently evaluated as a composite electrode for supercapacitors using either an acidic or an alkali solution as the electrolyte. The synthesis of the material involves mixing the purple corncob powder with different concentrations of KOH (in the range of 5% to 30%) and a thermal treatment at 700 °C under an inert atmosphere. Physicochemical characterizations were performed using scanning electron microscopy, Raman spectroscopy, N2 physisorption analysis, Fourier-transform infrared spectroscopy, and X-ray photoelectron spectroscopy, while the electrochemical characteristics were determined using cyclic voltammetry, a galvanostatic charge/discharge curve, and electrochemical impedance techniques measured in a three- and two-electrode system. Composite electrodes activated with 10% KOH had a specific surface area of 728 m2 g–1, and high capacitances of 195 F g–1 at 0.5 A g–1 in 1 mol L–1 H2SO4 and 116 F g–1 at 0.5 A g–1 in 1 mol L–1 KOH were obtained. It also presented a 76% capacitance retention after 50 000 cycles. These properties depend significantly on the microporous area and micropore volume characteristics of the activated carbon. Overall, our results indicate that purple corncob has an interesting prospect as a carbon precursor material for supercapacitor electrodes.